INFLUENCE OF IRRIGATION AND SOIL TEXTURE IN THE GROWTH OF PEACH TREE BRANCHES AND FRUITS OF cv. ESMERALDA1 - Monteiro, Alex Becker; Timm, Luís Carlos; Júnior, Carlos Reisser; Romano, Luciano Recart; Toebe, Marcos (IRRIGA, 2019)
INFLUENCE OF IRRIGATION AND SOIL TEXTURE IN THE GROWTH OF PEACH TREE BRANCHES AND FRUITS OF cv. ESMERALDA1 ALEX BECKER MONTEIRO2; LUÍS CARLOS TIMM3; CARLOS REISSER JÚNIOR4; LUCIANO RECART ROMANO5 E MARCOS TOEBE6 1 Part of Master’s Dissertation of the first author. 2 Departamento de Solos, Universidade Federal de Pelotas, Campus Universitário, s/n, CEP 96160-000, Pelotas, Rio Grande do Sul, Brasil, alexbeckermonteiro@gmail.com. 3 Departamento de Engenharia Rural, Universidade Federal de Pelotas, Campus Universitário, s/n, CEP 96160-000, Pelotas, Rio Grande do Sul, Brasil, lctimm@ufpel.edu.br. 4 Embrapa Clima Temperado, Rodovia BR 392, km 78, 9º Distrito, CEP 96010-971, Pelotas, Rio Grande do Sul, Brasil, carlos.reisser@embrapa.br. 5 Instituto Federal de Educação, Ciência e Tecnologia de Mato Grosso – Campus Cáceres, s/n, CEP 78200-000, Cáceres, Mato Grosso, Brasil, luciano.romano@cas.ifmt.edu.br. 6 Departamento de Ciências Agrônomicas e Ambientais, Universidade Federal de Santa Maria – Campus Frederico Westphalen, Linhas 7 de Setembro, s/n, BR386, km 40, CEP 98400-00, Frederico Westphalen, Rio Grande do Sul, Brasil, m.toebe@gmail.com. 1 ABSTRACT The objective of this work was to the evaluate the effect of irrigation and soil texture on the growth of branches and fruits of peach tree cv. Esmeralda. The study was developed in a commercial peach orchard, cv. Esmeralda, in Morro Redondo – Rio Grande do Sul state. Irrigated and non-irrigated plants were evaluated in two textural class (Sandy Loam and Sandy Clay Loam) in a total of four rows of peach. The irrigation management was based on the replacement of the potential crop evapotranspiration. The parameters of growth evaluated were: fruit growth and fruit growth rate, branch growth and branch growth rate. The results led to the conclusion that irrigation increases the diameter of the fruits of the peach crop by 5% in the Sandy Loam textural class and by 18% in the Sandy Clay Loam textural class; irrigation provides an increase in the size of the peach tree branches, especially after fruit harvesting, by 6% in the Sandy Loam textural class and 16% in the Sandy Clay Loam textural class; more clayey soils show the influence of irrigation more pronounced than in soils with higher sand contents as the soil of the present study, increasing fruit and branch growth. Keywords: Prunus persica (L.), irrigation management, peach orchard. MONTEIRO, A. B.; TIMM, L. C.; REISSER JÚNIOR, C.; ROMANO, L. R.; TOEBE, M. INFLUÊNCIA DA IRRIGAÇÃO E DA TEXTURA DO SOLO NO CRESCIMENTO DE RAMOS E FRUTOS DE PESSEGUEIRO DA cv. ESMERALDA 2 RESUMO O objetivo do trabalho foi avaliar o efeito da irrigação e da textura do solo no crescimento de ramos e frutos de pessegueiro cv. Esmeralda. O estudo foi conduzido em um pomar comercial de pessegueiro, cv. Esmeralda, no município de Morro Redondo - Rio Grande do Sul. Foram avaliadas plantas irrigadas e não irrigadas em duas classes texturais (Franco Arenosa e Franco Argilo Arenosa) num total de quatro linhas de pessegueiro. A irrigação foi manejada baseada na reposição da evapotranspiração potencial da cultura. Foram avaliadas as seguintes variáveis:crescimento e taxa de crescimento de frutos, e; crescimento e taxa de crescimento de ramos. A irrigação aumenta o diâmetro dos frutos da cultura do pessegueiro em 5% na classe textural Franco Arenosa e em 18% na classe textural Franco Argilo Arenosa; a irrigação proporciona aumento no tamanho dos ramos da cultura do pessegueiro, principalmente após a colheita dos frutos, em 6% na classe textural Franco Arenosa e em 16% na classe textural Franco Argilo Arenosa; solos de textura mais argilosa mostram a influência da irrigação mais pronunciadamente do que em solos com teores de areia mais elevados como o solo do presente estudo, incrementando o crescimento de frutos e ramos. Palavras-chave: Prunus persica (L.), manejo da irrigação, persicultura.